Organofunctionalization of vanadium(III) acetylacetonate complex over aminofunctionalized SBA-15 for sulfoxidation reactions - Lazar, Anish; Sanjush, K. S.; Singh, A. P. (Advanced Porous Materials, 2016)
Recyclable SBA-15 supported aminopropyl vanadium(III) acetylacetonate heterogeneous catalyst has been synthesized by covalent anchoring of vanadium(III) acetylacetonate over aminofunctionalized SBA-15 via. post grafting method, V(III)(acac)3NH2@SBA-15. The synthesized catalyst was characterized by elemental analysis, ICP-OES, XRD, N2 sorption analysis, FT-IR, 29Si NMR spectroscopy, XPS, SEM and TEM. The percentage of nitrogen and vanadium in V(III)(acac)3NH2@SBA-15 was determined by elemental analysis and ICP-OES, respectively. XRD and N2 sorption analyses provide the information about the structural integrity (Mesoporous structure) and textural properties of all synthesized catalysts. The presence and degree of organofunctionalization on SBA-15 were monitored by FT-IR and 29Si NMR spectroscopy, respectively. Moreover, the oxidation state and the chemical environment of vanadium metal in V(III)(acac)3NH2@SBA-15 were revealed by XPS spectroscopy. Eventually, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalyst was evaluated in oxidation of various sulfides and the results show that V(III)(acac)3NH2@SBA-15 catalyst exhibits higher conversion and selectivity towards the sulfoxidation reaction compared to the neat V(III)(acac)3 complex and blank reaction. The synthesized catalyst was recycled four times.